Continuity of Care Implementation for Mrs. R at Al Islam H.M. Mawardi Hospital: Pelaksanaan Asuhan Kesinambungan pada Ny. R di Rumah Sakit Al Islam H.M. Mawardi - Rafi, Zahro Firdausa; Widowati, Hesty; Purwanti, Yanik (Universitas Muhammadiyah Sidoarjo, 2025)
The Maternal Mortality Rate (MMR) in East Java Province was significantly reduced in 2020 but is still far from the SDGs target. Continuity of Care is a healthcare approach continuously starting from pregnancy, childbirth, postpartum, newborns, and family planning. The purpose of this case study is to describe the implementation of CoC at Al Islam H.M. Mawardi Hospital during pregnancy to postpartum. Method : midwivery descriptive method, Mrs. R was given care from the third trimester of pregnancy up to family planning method. Result : The implementation of CoC on Mrs. R was in accordance with the standard of physiological midwivery care and the treatment went well without any pathological conditions. Low back pain is a frequent condition in pregnancy, Ny. R was given accupressur on hegu point to relieve the pain. Conclusion : The care provided to the research subjects has been adjusted to the standards of midwifery care and the condition of the mother and baby and it worked physiologically. Highlights: Continuity of Care (CoC): The implementation of CoC from pregnancy to family planning at Al Islam H.M. Mawardi Hospital followed standard physiological midwifery practices. Effective Pain Management: Mrs. R experienced low back pain during pregnancy, which was relieved through acupressure on the hegu point. Physiological Care Success: The care provided aligned with midwifery standards, ensuring the well-being of both the mother and baby without complications. Keywords: Pregnancy, Childbirth, Postpartum, Newborn, Contraception